If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-6x=-33-14x
We move all terms to the left:
7-6x-(-33-14x)=0
We add all the numbers together, and all the variables
-6x-(-14x-33)+7=0
We get rid of parentheses
-6x+14x+33+7=0
We add all the numbers together, and all the variables
8x+40=0
We move all terms containing x to the left, all other terms to the right
8x=-40
x=-40/8
x=-5
| 2b-24=68+180 | | X2+2x+1=100 | | 11=23(8x+12)32 | | 11= 23(8x+12)32 (8x+12) | | 6(4x-3)=8(3x-2) | | 0.14(x+1000)=5740 | | 18-5x=10-3x | | 6(7-5)=2(10+3y) | | 0.11(x+1000)=5060 | | 24/16=n/6 | | F(x)=2x^2+4x+8 | | 5x+1=12x+2 | | -12-6x=8x+2x | | -12x-6x=8x+2x | | (5x)(x-2)(10)=0 | | 7(a+6)=252 | | 2t+26=11t+41 | | H=16t^2+84t+5 | | 3/5x=1/2*250 | | 6 | | -1+5^(3x+4)=124 | | 4x=x+99 | | -1+5^3x+4=124 | | 3b-46=b | | 17t+32=15t-12 | | 18-(x+4)^2=2 | | (x-28)°=90 | | 6+4x=x-12 | | 2p+14=7p-32 | | 3+4d-14=15-5d-14 | | x+(x-35)=137 | | 11y+36=15y-12 |